How Much of Language Acquisition Does Operant Conditioning Explain? - Sturdy, Christopher B.; Nicoladis, Elena (Frontiers in Psychology, 2017)
Since the 1950s, when Chomsky argued that Skinner’s arguments could not explain syntactic acquisition, psychologists have generally avoided explicitly invoking operant or instrumental conditioning as a learning mechanism for language among human children. In this article, we argue that this is a mistake. We focus on research that has been done on language learning in human infants and toddlers in order to illustrate our points. Researchers have ended up inventing learning mechanisms that, in actual practice, not only resemble, but in fact are, examples of operant conditioning by any other name they select. We argue that language acquisition researchers should proceed by first ruling out operant conditioning before invoking alternative learning mechanisms. While it is possible that operant conditioning cannot explain all of language acquisition, simple learning mechanisms that work across species may have some explanatory power in children’s language learning.